PENENTUAN BIAYA TRANSPORTASI MINIMUM PADA PEMILIHAN RUTE PENGIRIMAN MENGGUNAKAN METODE CLARK AND WRIGHT SAVING HEURISTIC - Muh. Mufid Siraj; Yuliani Puji Astuti (MATHunesa: Jurnal Ilmiah Matematika, 2020)
The transportation system has a very important role in service to each customer because it must guarantee product mobility and at the same time be able to minimize transportation costs. In the distribution process in general, various problems arise, one of which is the problem of shipping routes so that transportation costs are less than optimal. Problems with suboptimal delivery routes are included in the Vehicle Routing Problem. For this reason, it is necessary to optimize the shipping route with an appropriate method. The method used in this study is the Clark and Wright Saving Heuristic method. This paper discusses the determination of minimum transportation costs in the selection of shipping routes using the Clark and Wright Saving Heuristic method for coffee delivery. The results of applying this method to the company's problems obtained optimal routes and transportation costs incurred are also optimal. The total distance and transportation costs of the company are 12,551.4 km and Rp. 22,550,372.-. While the total mileage and transportation costs using the Clark and Wright Saving Heuristic method are 7,324.3 km and Rp. 12,777,454, -. Thus if the Clark and Wright Saving Heuristic method is applied in the company, it will minimize the total mileage and transportation costs incurred.